Uses of literature from different sources in music education research: some issues (Orfeu, 2022)
This essay discusses research in music education regarding to the appropriation of specialized literature in the works. From an initial discussion on the notion of scientific theory and its academic value, it also raises the question of epistemological coherence as an important aspect of research reliability. Inquiring the status of the various bibliographic sources mobilized in an investigative work, it proposes a way of organizing this material that allows different functions of different texts used to be made explicit even in the way of writing. With no intention of providing a model as the best, much less closing the question, it is believed, however, that a concern with the issues addressed here may qualify research and research evaluations in the area.
Keywords: music education research; scientific theory; epistemology